2016
DOI: 10.4238/gmr.15027869
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation between Triatoma arthurneivai and Triatoma wygodzinskyi (Hemiptera: Reduviidae: Triatominae) using cytotaxonomy

Abstract: ABSTRACT. Using classic morphometric techniques to examine the head and thorax of Triatoma specimens, researchers identified a possible taxonomic problem involving T. arthurneivai (Lent & Martins) and T. wygodzinskyi (Lent). A recent geometric morphometric study indicated that the insects captured outside the Serra do Cipó region, State of Minas Gerais, Brazil, were T. wygodzinskyi. The misidentification of T. arthurneivai as T. wygodzinskyi could result in several problems associated with entoepidemiological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Cytogenetic studies have provided insight into reproductive [39][40][41], physiological [42,43], evolutionary [44][45][46], systematic [34,47], and taxonomic [33,36,48] aspects of Triatominae. Cytotaxonomy was initially developed in 1950, when Schreiber and Pellegrino [49] described some karyotypes of species from South America.…”
Section: Resultsmentioning
confidence: 99%
“…Cytogenetic studies have provided insight into reproductive [39][40][41], physiological [42,43], evolutionary [44][45][46], systematic [34,47], and taxonomic [33,36,48] aspects of Triatominae. Cytotaxonomy was initially developed in 1950, when Schreiber and Pellegrino [49] described some karyotypes of species from South America.…”
Section: Resultsmentioning
confidence: 99%
“…25 Recently, the heterochromatin pattern and the composition of AT and CG was one of the tools used to describe R. taquarussuensis Rosa et al 27 However, molecular analyzes and experimental crosses showed that R. taquarussuensis was R. neglectus with chromosomal polymorphisms. 28 Based on this, it is evident that although cytogenetic analyses are of great taxonomic importance, 29,30 the confirmation that different cytotypes represent valid taxa must be performed through integrative taxonomy. 31 Thus, we characterize the AT-and CG-rich DNA pattern for the genus Rhodnius, and we suggest that the pattern of CG-rich heterochromatin in the autosomes of these vectors evolved independently in pallescens, pictipes, and prolixus groups.…”
mentioning
confidence: 99%
“…13,14 However, problems in correctly identifying species can lead to an incorrect panorama of distribution of Chagas disease vectors as 15 demonstrated that the species that exists in São Paulo is Triatoma wygodzinsky (Lent, 1951) that was incorrectly identified as T. arthurneivai (endemic to the state of Minas Gerais). 5 Cytogenetic tools are contributing to the taxonomy of triatomines; for example, Alevi et al 16 recently characterized the prophase cells of T. arthurneivai and T. wygodzinsky and differentiated the species easily, highlighting the applicability of the cytological analyzes in the correct identification of the species. Based on this information, we developed an identification key for the triatomines of the state of São Paulo, based on cytogenetic data.…”
mentioning
confidence: 99%